2022
DOI: 10.3389/fimmu.2022.762390
|View full text |Cite
|
Sign up to set email alerts
|

B Cell IL-4 Drives Th2 Responses In Vivo, Ameliorates Allograft Rejection, and Promotes Allergic Airway Disease

Abstract: B cells can be polarized to express various cytokines. The roles of IFNγ and IL-10, expressed respectively by B effector 1 (Be1) and Bregs, have been established in pathogen clearance, tumor growth, autoimmunity and allograft rejection. However, the in vivo role of B cell IL-4, produced by Be2 cells, remains to be established. We developed B-IL-4/13 iKO mice carrying a tamoxifen-inducible B cell-specific deletion of IL-4 and IL-13. After alloimmunization, B-IL-4/13 iKO mice exhibited decreased IL-4+ Th2 cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 51 publications
(74 reference statements)
0
8
0
Order By: Relevance
“…IL-4, mainly secreted by Th2 cells [ 31 , 32 ], plays a critical role in asthma as a characteristic factor of Th2 cell subsets. IL-4 acts on B lymphocytes to produce IgE and induce a shift from IgM to IgE antibodies produced by B cells, contributing to the asthmatic response [ 33 ]. Th2 cells directly trigger the aggregation and activation of inflammatory cells by releasing IL-4, IL-5, IL-13, and other cytokines, and promote the occurrence of delayed airway allergic reactions.…”
Section: Discussionmentioning
confidence: 99%
“…IL-4, mainly secreted by Th2 cells [ 31 , 32 ], plays a critical role in asthma as a characteristic factor of Th2 cell subsets. IL-4 acts on B lymphocytes to produce IgE and induce a shift from IgM to IgE antibodies produced by B cells, contributing to the asthmatic response [ 33 ]. Th2 cells directly trigger the aggregation and activation of inflammatory cells by releasing IL-4, IL-5, IL-13, and other cytokines, and promote the occurrence of delayed airway allergic reactions.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that intravenous administration of a humanized anti-human IL-5 monoclonal antibody reduced the size of nasal polyps [25,26]. IL-4 determines the polarization of CD4 cells to effector Th2 cells and is an essential factor for immunoglobulin E (IgE) production [27][28][29]. IL-13 is found to be associated with mucous gland hyperplasia and epithelial remodeling [30,31].…”
Section: Excessive Type 2 Inflammatory Response In Ar and Crswnpmentioning
confidence: 99%
“…22 In various preclinical transplantation models, IL-4 treatment or secretion has been shown to promote allograft survival, which was attributed to promotion of Th2 responses and reduction in Th1 frequency, 23 whilst also expanding the Treg compartment. 24 Additionally, promotion of Th2 subset predominance, whether intentional or as an off-target effect of an intervention, has been shown to ameliorate rejection in several mouse models. [25][26][27] An association between improved graft health and lowered rejection grades and a Th2-favoring shift in the Th1/Th2 balance has been demonstrated, emphasizing the potential importance of this subset balance.…”
Section: Cd4 + Th2 Subtypementioning
confidence: 99%